2017
DOI: 10.3389/fneur.2017.00255
|View full text |Cite
|
Sign up to set email alerts
|

Alexander Disease Mutations Produce Cells with Coexpression of Glial Fibrillary Acidic Protein and NG2 in Neurosphere Cultures and Inhibit Differentiation into Mature Oligodendrocytes

Abstract: BackgroundAlexander disease (AxD) is a rare disease caused by mutations in the gene encoding glial fibrillary acidic protein (GFAP). The disease is characterized by presence of GFAP aggregates in the cytoplasm of astrocytes and loss of myelin.ObjectivesDetermine the effect of AxD-related mutations on adult neurogenesis.MethodsWe transfected different types of mutant GFAP into neurospheres using the nucleofection technique.ResultsWe find that mutations may cause coexpression of GFAP and NG2 in neurosphere cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…The cytoplasmic accumulations of GFAP and Rosenthal fibers in astrocytes cause proteasome inhibition, stress kinase activation, mechanistic target of rapamycin activation, loss of glutamate‐ and potassium‐buffering capacity, loss of astrocyte coupling, and changes in cell morphology (Olabarria & Goldman, ). They together increased caspase 3 activity (Gomez‐Pinedo, Sirerol‐Piquer, Duran‐Moreno, Garcia‐Verdugo, & Matias‐Guiu, ) lead to increased apoptosis of astrocytes and their nearby neurons.…”
Section: Gfap and Neurological Diseasesmentioning
confidence: 99%
“…The cytoplasmic accumulations of GFAP and Rosenthal fibers in astrocytes cause proteasome inhibition, stress kinase activation, mechanistic target of rapamycin activation, loss of glutamate‐ and potassium‐buffering capacity, loss of astrocyte coupling, and changes in cell morphology (Olabarria & Goldman, ). They together increased caspase 3 activity (Gomez‐Pinedo, Sirerol‐Piquer, Duran‐Moreno, Garcia‐Verdugo, & Matias‐Guiu, ) lead to increased apoptosis of astrocytes and their nearby neurons.…”
Section: Gfap and Neurological Diseasesmentioning
confidence: 99%
“…Besides, the decreased ability to buffer glutamate and potassium, as well as elevated levels of cytokines and chemokines, of AxD astrocytes could also result in neuronal dysfunction (such as more sensitive to glutamate-generated death and more depolarized) and oligodendrocyte degeneration (such as toxicity and loss of myelin) (Deng et al, 2006; Olabarria and Goldman, 2017). Meanwhile, AxD-associated GFAP mutations would inhibit the proliferation and terminal differentiation of OPCs (Gomez-Pinedo et al, 2017; Li et al, 2018). Our study here suggested an impairment in intercellular mitochondrial transfer between GFAP-mutated astrocytes and from these astrocytes into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Es especialmente interesante la utilización de cultivos de células precursoras de oligodendrocitos o de células neurales indiferenciadas, ya que nos permiten evaluar los procesos de diferenciación, observar el efecto de factores inflamatorios, testar nuevos compuestos químicos destinados a favorecer la proliferación de los oligodendrocitos 6 , así como desarrollar estrategias que ayuden a mejorar el proceso de remielinización 14 . Nuestro grupo ha utilizado estas células para transfectar mutaciones asociadas a la enfermedad de Alexander y conocer los mecanismos de la mielinización en esta enfermedad 15 . Los cultivos primarios de astrocitos son también interesantes ya que estas células participan en el ambiente local, el cual es imprescindible en el proceso de remielinización, actuando mediante la secreción de factores de crecimiento como el factor de crecimiento derivado de plaquetas o el factor de crecimiento insulínico tipo 1, los cuales han mostrado que promueven la remielinización.…”
Section: Desarrollo Modelos In Vitrounclassified